Universidades corporativas: modelo de avaliação do perfil institucional em organizações instaladas na região metropolitana de Fortaleza (CE) - Maciel, Ilana Maria de Oliveira (2023)
Amidst accelerated development, grounded in knowledge management as a pathway for professional advancement under the "umbrella" of corporate education, the relevance of an in-depth study about one of the tools used by organizations in the corporate market, contributing to the training, qualification, and improvement of the workforce and other stakeholders in their Corporate Universities, was realized. In this perspective, an attempt was made to construct a thesis in which the structure was consolidated considering De Bruyne, Herman, and De Schoutheete's (1977) quadripolar methodology, featuring four interdependent and dialogical poles, which, even though structured in a segmented way, should connect in the epistemological, theoretical, morphological, and technical construction of the investigated subject. In this case, the epistemological framework focused on the origin and evolution of formal, informal, and non-formal education, corporate education, educational evaluation involving its four generations disseminated by Guba; Lincoln (1989), and more recently, the 5th generation of educational evaluation observing relationships based on the individual and collective actions of social agents (Lima Filho; Trompieri Filho, 2012). The theoretical pole that covers the entire theoretical trajectory in which the model of corporate universities, corporate education, and its andragogical implications consolidated in order to demonstrate how the models identified in the morphological pole, with the exposition of steps and dimensions, according to the essential structures defined throughout the mapping of the profile of these non-formal education organizations described in the technical pole, which resulted in 10 (ten) essential structures, 38 (thirty-eight) second-level structures, and 44 (forty-four) indicators, according to Lima's (2008) systemic structuring theory, which underpin the models of universities. Based on the segmented and constructed information across the epistemological, theoretical, and morphological poles, a form applicable for the validation of a scale was developed and proposed in the technical pole, aiming to trace an institutional profile of corporate universities aligned with regional and local differences from a pre-test round with the object under study and applied in field research in 8 (eight) Corporate Universities in the segments: industry, services, and commerce, being of extreme importance due to its novelty in the market and academia as non-formal education. As a significant contribution to society, a scale was constructed, applied, and validated with the UCs, uniquely outlining a profile othese organizations which will be available for further research, defining the guiding structures for the establishment or reorganization of UCs in Ceará.